Interakce kmenových buněk s polymerním substrátem - Slepičková Kasálková, Nikola; Slepička, Petr; Bačáková, Lucie; Kolská, Zdeňka; Švorčík, Václav (Chemické listy, 2017)
This work is aimed on the determination of physico-chemical properties of plasma treated poly-L-lactic acid biopolymer and its influence on the attachment and organization of stem cells from fat tissue. The surface changes were examined with goniometry (wettability), atomic force microscopy (surface roughness and morphology) and photoelectron spectroscopy (chemical changes). The cytocompatibility of PLLA was studied in vitro by characterization of stem cell adhesion, growth, differentiation, migration and proliferation. The physico-chemical properties depend strongly on the plasma treatment time. It was found that plasma activation has a positive effect on stem cells cultivation, as well as on the cell growth in orderly manner and in the preferred direction.
Keywords: Polymers; povrchové vlastnosti; Stem Cells; výzkum kmenových buněk; povrchová modifikace; cytokompatibilita; polymery; kmenové buňky; Stem Cell Research; Surface Properties